The role of digital technologies in enhancing inclusive education: A systematic review of current trends - Teng, Kie Yin; Liden, Anthea Yulticia; John Girrie, Cassandra Racha; Dinggat, Jasnita Naja; Lee, Hou Yew (Jurnal Pendidikan Bitara UPSI, 2025)
The integration of digital technologies in Inclusive Education (IE) has gained significant momentum in recent years, enhancing accessibility, engagement, and personalised learning for diverse learners, including students with Special Educational Needs (SEN). This small-scale systematic review explores the latest trends in digital applications supporting IE, drawing on studies published between 2020 and 2025. Five major academic databases—Scopus, Web of Science, Google Scholar, IEEE Xplore, and Wiley Online Library—were used to identify peer-reviewed literature aligned with the objectives of the review. Adherence to the PRISMA framework enhanced the transparency and replicability of the review process. Key emerging trends include assistive technologies such as speech-to-text and text-to-speech tools, AI-driven personalised learning systems, and game-based learning platforms that support students with SEN. Additionally, immersive technologies such as augmented reality (AR) and virtual reality (VR) are fostering interactive and differentiated instruction, enhancing learning experiences for students with SEN. Mobile learning and cloud-based platforms are also promoting universal design for learning (UDL) principles, ensuring flexibility in content delivery. However, challenges such as the digital divide, teacher training gaps, and concerns over data privacy remain. Addressing these challenges requires strategic investments in infrastructure, professional development, and ethical policies to optimise digital inclusivity. The findings suggest that a thoughtful integration of digital tools can significantly improve inclusivity in education, fostering equity and engagement for all learners. Future research should explore how emerging technologies, such as AI-driven adaptive learning and blockchain-based credentialing, can further enhance inclusive digital education. This review contributes to the growing body of literature on digital inclusivity and highlights implications for policymakers, educators, and researchers seeking to improve accessibility and learning outcomes in diverse educational settings.